Differential expression of low density lipoprotein receptor–related protein 1 (LRP-1) and matrix metalloproteinase-9 (MMP-9) in prostate gland: From normal to malignant lesions - Gilardoni, Mónica Beatriz (2017)
Background Metalloproteinases (MMPs) are relevant modulators of inflammation, tumor microenvironment, cancer invasion and metastasis. They can be regulated by the Low density lipoprotein Receptor?related Protein 1 (LRP-1), a receptor reported to mediate the clearance of lipoproteins, extracellular matrix (ECM) macromolecules and proteinases. The aim of this study was to evaluate the expression of LRP-1, MMP-2 and MMP-9 across various grades of prostatic diseases as benign prostatic hyperplasia (BPH), BPH plus prostatitis (BPH + P), high grade prostatic intraepithelial neoplasia (HGPIN) and prostate cancer (PCa). Methods LRP-1 was analyzed using immunohistochemistry and MMPs proteolytic activity by zymography in prostate tissues with different prostatic diseases. Results LRP-1 was detected in epithelial cells in BPH (16/18), BPH + P (21/21) and HGPIN (6/6), with a staining intensity of 1+, 1+/2+ and 3+, respectively. In PCa, LRP-1 was absent in 19/27 samples while a low expression was observed in 8/27 biopsies. MMP-9 activity was higher and statistically significant in PCa than in BPH (p ≤ 0.01). Conclusion Considering that LRP-1, by mediating the clearance of MMPs, is involved in the regulation of ECM remodeling and cell migration, we conclude that a decreased expression of LRP-1 could be involved with the increasing activity of MMPs shown in cancers.